Reconstructing Indonesian Democracy: A Critique of the One-Man-One-Vote Model and the Idea of ​​Tiered Pancasila Democracy - Rinto Setiyawan; Alessandro Rey Nearson; Prayogi Restia Saputra (International Journal of Education, Information Technology, and Others, 2026)
Modern democracy based on the one-man-one-vote principle emphasizes formal equality in political participation, yet it is often criticized for failing to ensure the quality of leadership it produces. In the Indonesian context, the dominance of political parties in the nomination process and the influence of oligarchic structures indicate a gap between the principle of popular sovereignty and the actual practice of democracy. This study aims to reconceptualize Indonesia’s democratic model to better align with the values of Pancasila through a tiered democracy approach.This research employs a normative legal method with a doctrinal approach, examining primary legal sources such as the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 and related regulations, as well as recent academic literature. The analysis is conducted qualitatively using interpretative and argumentative methods within the framework of deliberative democracy theory. The findings indicate that procedural democracy tends to produce leadership driven by popularity and economic power rather than substantive quality. Therefore, a reconstruction of the democratic system is necessary through a tiered mechanism, in which the initial selection of leadership candidates is carried out by constitutionally legitimate state institutions before being submitted to general elections. This model does not diminish popular sovereignty but rather strengthens it by ensuring that political choices remain within the framework of leadership quality. This study contributes to the development of a more substantive conception of Pancasila democracy and offers normative recommendations for reforming Indonesia’s political system